Ensaios em desenvolvimento e crescimento econômico - Ribeiro, Felipe Garcia (2013)
This thesis consists of three essays, one being on economic development and the two others on economic growth. The first essay is an investigation into how access to electricity by households affects time allocation of children and teenagers from rural Brazil in what regards the choice to attend school or to engage in the labor market. To establish a causal relationship between the availability of electricity and time allocation, we use the criteria of priority works from Luz Para Todos program as a source of exogenous variation in access to electricity of households located in rural Brazil. We apply Regression Discontinuity Design and Difference in Difference estimator with endogenous variables. The results from the latter methodology indicate that the presence of electricity increases the likelihood that children and adolescents are enrolled in school and are not delayed relative to the grade they should be attending at their age. Also, the probability of a child being literate and not being working increases with the presence of electricity. One of the possible channels that could explain these results is the increased participation of mothers in the labor market. However, one cannot discard the hypothesis that the observed results are justified by the increased access to electricity by the schools, making them better and more attractive to students and by the receipt of Bolsa Familia program which is conditional on school attendence by children and teenagers. The second study aims to contribute to the literature on institutions and economic growth through the investigation of how the 1959 socialist revolution in Cuba have affected the trajectory of per capita income in that country. To do so, we apply the synthetic control method to obtain the counterfactual path of income per capita in the absence of such revolution. The results show that the trajectory of the annual GDP per capita of Cuba between 1959 to 1980 was lower than it would have been if the socialist regime had not been implemented. This result is robust to different placebo tests deployed and also to the use of different series of GDP per capita. Alternative hypotheses that could explain the lower path of GDP per capita are discussed based on the existing literature and data. The discussion suggests that institutional change was indeed the cause of the observed negative effect on the Cuban economy during the period of analysis. Finally, the third article investigates the economic cost of a natural disaster in Brazil. The paper looks at the excessive rains that happened in the state of Santa Catarina in November and December 2008. This study contributes with some new evidence to the iv recent literature on natural disasters. To our knowledge, there are no studies in Brazil that empirically measure the impact that a natural disaster has entailed on an affected region. This study is structured in two parts. The first uses synthetic control to measure the impact of rainfall on the industrial production of Santa Catarina. For that, we propose a small accommodation method for treating the effects of possible flooding rains in other states. In the second part, we use the method of difference in difference to measure the impact of the rains on the GDP per capita of the cities. The results show that for a period of two years after the end of 2008, the impact of the rains caused a lower monthly industrial production of 2.0% in Santa Catarina. For municipalities, the estimated effect of the disaster on GDP per capita was around -7.0% in 2008 and -5.0% in 2009. There was not significant effect in 2010.